In Systemic Sclerosis, a Unique Long Non Coding RNA Regulates Genes and Pathways Involved in the Three Main Features of the Disease (Vasculopathy, Fibrosis and Autoimmunity) and in Carcinogenesis - Dolcino, Marzia (J Clin Med, 2019)
Systemic sclerosis (SSc) is an autoimmune disease characterized by three main features: vasculopathy, immune system dysregulation and fibrosis. Long non-coding RNAs (lncRNAs) may play a role in the pathogenesis of autoimmune diseases and a comprehensive analysis of lncRNAs expression in SSc is still lacking. We profiled 542,500 transcripts in peripheral blood mononuclear cells (PBMCs) from 20 SSc patients and 20 healthy donors using Clariom D arrays, confirming the results by Reverse Transcription Polymerase-chain reaction (RT-PCR). A total of 837 coding-genes were modulated in SSc patients, whereas only one lncRNA, heterogeneous nuclear ribonucleoprotein U processed transcript (ncRNA00201), was significantly downregulated. This transcript regulates tumor proliferation and its gene target hnRNPC (Heterogeneous nuclear ribonucleoproteins C) encodes for a SSc-associated auto-antigen. NcRNA00201 targeted micro RNAs (miRNAs) regulating the most highly connected genes in the Protein-Protein interaction (PPI) network of the SSc transcriptome. A total of 26 of these miRNAs targeted genes involved in pathways connected to the three main features of SSc and to cancer development including Epidermal growth factor (EGF) receptor, ErbB1 downstream, Sphingosine 1 phosphate receptor 1 (S1P1), Activin receptor-like kinase 1 (ALK1), Endothelins, Ras homolog family member A (RhoA), Class I Phosphoinositide 3-kinase (PI3K), mammalian target of rapamycin (mTOR), p38 mitogen-activated protein kinase (MAPK), Ras-related C3 botulinum toxin substrate 1 (RAC1), Transforming growth factor (TGF)-beta receptor, Myeloid differentiation primary response 88 (MyD88) and Toll-like receptors (TLRs) pathways. In SSc, the identification of a unique deregulated lncRNA that regulates genes involved in the three main features of the disease and in tumor-associated pathways, provides insight in disease pathogenesis and opens avenues for the design of novel therapeutic strategies.